Kepuasan Konsumen Serra Serri Restoran yang Dipengaruhi Kualitas Produk, Servicescapes, dan Lifestyle - Muhammad Rafi' Ramadhan; Aris Budiono (LPPM Universitas Asa Indonesia, 2026)
This study aims to analyze the influence of product quality, servicescapes, and lifestyle on consumer satisfaction at Serra Serri Restaurant in Jakarta, which operates within the highly competitive urban restaurant industry. A quantitative approach is employed, using a survey of 125 consumers selected through probability sampling, while an additional 20 respondents are used to test the validity and reliability of the Likert‑scale questionnaire instrument. The findings reveal that product quality, servicescape, and lifestyle collectively have a positive and significant effect on consumer satisfaction. Individually, product quality and lifestyle show a statistically significant positive influence, whereas servicescape has a positive effect but does not reach significance at the 5% level. These results indicate that improving product quality and aligning the restaurant’s concept with consumers’ lifestyles should be the main priorities for enhancing satisfaction, while the management of servicescapes still needs further optimization so that all three aspects can work synergistically to increase satisfaction, repeat visits, and potential customer loyalty